Effects of whole maize high-grain diet feeding on colonic fermentation and bacterial community in weaned lambs - Cheng, Chao; Yin, Yuyang; Bian, Gaorui (Frontiers in Microbiology, 2022)
To investigate the effects of maize form in high-grain diets on colonic fermentation and bacterial community of weaned lambs, twenty-two 2.5-month-old healthy Hu lambs were randomly divided into three groups: a maize meal low-grain diet feeding group (19.2% grain; CON), a maize meal high-grain diet feeding group (50.4% grain; CM), and a whole maize high-grain diet feeding group (50.4% grain; CG). After 7 weeks of feeding, the total volatile fatty acid concentration (P = 0.035) were significantly higher in lambs from CM than that from CON. There was no significant difference of colonic fermentation parameters between CM and CG (P > 0.05) group. The results of colonic content microbial composition revealed that the relative abundance of genera Parasutterella (P = 0.028), Comamonas (P = 0.031), Butyricicoccus (P = 0.049), and Olsenella (P = 0.010) were higher in CM than those in CON; compared with CM, the CG diet had the higher relative abundance of genera Bacteroides (P = 0.024) and Angelakisella (P = 0.020), while the lower relative abundance of genera Olsenella (P = 0.031) and Paraprevotella (P = 0.006) in the colonic content. For colonic mucosal microbiota, the relative abundance of genera Duncaniella (P = 0.024), Succiniclasticum (P = 0.044), and Comamonas (P = 0.012) were significantly higher in CM than those in CON. In comparison, the relative abundance of genera Alistipes (P = 0.020) and Campylobacter (P = 0.017) were significantly lower. And the relative abundance of genera Colidextribacter (P = 0.005), Duncaniella (P = 0.032), Christensenella (P = 0.042), and Lawsonibacter (P = 0.018) were increased in the CG than those in the CM. Furthermore, the CG downregulated the relative abundance of genes encoding infectious-disease-parasitic (P = 0.049), cancer-specific-types (P = 0.049), and neurodegenerative-disease (P = 0.037) in colonic microbiota than those in the CM. Overall, the present study indicated that maize with different grain sizes might influence the colonic health of weaned lambs by altering the composition of the colonic bacterial community.